(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Life is not always smooth sailing. Human life is full of ups and downs andpeople become easily perturbed and stressed while facing problems of any sort in different facets of life. Sitting idle cannot solve problems but, it is best to control emotional equilibrium so that one finds out the most pertinent solution to reduce stress and to solve problems as and when required. Environment sometimes enacts very effectively in stress management and reduction process. It is a kind of healthy reciprocation between the humans and environment where they live or even interact with each other for overall betterment. This healing mutualism among the humans and environmental components is be termed as Ecopsychology, which treats people psychologically by bringing them spiritually closer to nature. This article explores and introspect the concept-related issues and implications of Ecopsychology precisely.